Conflict Theory, Extended: A Framework for Understanding Contemporary Struggles Over Education Policy. Issue 3 (May 2023) - Ferrare, Joseph J.; Phillippo, Kate
Conflicts over education and education policy continue, and now new, diversified actors push for change while technologies expand the terrain where conflicts unfold. Conflict theories would seem best suited to address these conflicts. However, despite conflict theories' substantive contributions, they are infrequently used in the US context and have met with critique, viewed as too reductive to fully contend with the complexities of conflict in the educational arena. In this paper, we extend traditional conflict theories to address these longstanding critiques and to also incorporate contemporary complexities and developments. Our study is grounded in recent developments in sociological field theory and intersectionality theory. Our proposed extension of conflict theory was developed in conversation with twelve empirical cases of recent conflicts in P-16 education. This iterative project's novel insights offer practical implications for policy actors, researchers, and policymakers.